University-community partnerships for promoting social responsibility in higher education - Sengupta, Enakshi; Blessinger, Patrick; Mahoney, Craig (Innovations in higher education teaching and learning ;, 2020)
This book provides empirical evidence on how universities have considered social responsibilities as their prime focus, and engaged with civil society to enhance their values. Case studies from Indonesia to the United Kingdom enrich the book through experience, interventions and narratives.